The Impact of Electromagnetic Field Exposure on Diabetes: A Narrative Review - Behzad Fouladi Dehaghi; Masoomeh Vahabi Shekarloo; Ameneh Golbaghi; Leila Ibrahimi Ghavamabadi (Journal of Environmental Health and Sustainable Development)
Introduction: This literature review investigates the complex relationship between electromagnetic fields (EMFs) and diabetes, highlighting both therapeutic potentials and associated health risks. Emerging evidence suggests that exposure to specific types of EMFs, particularly pulsed EMFs (PEMF), may enhance insulin sensitivity and promote healing in diabetic patients. Materials and Methods: Studies have indicated significant improvements in microvascular blood flow and pancreatic function, suggesting a potential role for EMF therapy in diabetes management. Conversely, prolonged exposure to high-frequency EMFs, such as those that cell phones emanate and wireless devices, raises concerns regarding their impact on glucose metabolism. Results: A correlation was observed between chronic EMF exposure and increased insulin resistance, oxidative stress, and disruptions in hormonal balance, which can exacerbate hyperglycemia. Mechanistic insights reveal that elevated levels of reactive oxygen species (ROS) and alterations in cortisol and glucagon levels may contribute to these adverse effects. Conclusion: Despite the promising therapeutic applications of certain EMFs, the existing literature presents significant variability in methodologies, limiting the generalizability of findings. Future research should focus on large-scale, longitudinal studies that encompass diverse populations to clarify the long-term effects of EMF exposure on diabetes. This review underscores the need for a balanced approach to EMF exposure, recognizing both its potential benefits and risks for individuals with diabetes, thereby informing clinical practices and public health policies.